Developing Resilience to Emergencies: Evaluation of Thermal Indices and Outdoor Comfort Before and During the COVID-19 Pandemic - Adekunle, Timothy O. (Frontiers in Built Environment, 2021)
This research discusses thermal indices and outdoor comfort before and during the Coronavirus Disease of 2019 (COVID-19) pandemic in three counties in Connecticut, USA. Existing research noted that people residing in highly populated urban and low-income areas are disproportionately affected by the pandemic and subject to health, heat, and cold stress-related problems. The study is motivated to examine outdoor comfort and thermal indices in the counties that account for over 75% of the population in the state. The aim of the study is to examine outdoor comfort and thermal indices a year before and during the pandemic to determine if the pandemic significantly affects occupants and their overall well-being. The research questions include (i) Does the pandemic year provide a more comfortable thermal environment for outdoor occupants than the period before the pandemic? (ii) Does the period provide a cleaner environment with no thermal or cold stress to occupants than before the pandemic? The research approaches include the field data recorded in 2019 and 2020. The research also utilized observations and mathematical models. The findings revealed that the mean monthly temperatures varied from -3.2°Cto25.2°C and relative humidity ranged from and 62.6%-70.7%. The study revealed cold stress in wintertime. Heat stress is also noted in summertime across the counties. New Haven is more prone to heat stress than other counties because of some factors (such as climate change, etc.). Higher thermal indices are reported in 2020 than the indices computed for 2019 which could influence thermal comfort, health, and well-being of people. The indices are strongly influenced by outdoor temperatures and dew-point. A combination of some environmental variables such as temperature and wind speed also have significant effects on the indices. The study recommends that the use of clean energy for running infrastructure systems would help in mitigating the impact of climate change in various locations. The investigation suggests that a thorough evaluation of environmental conditions and interventions should be explored for developing resilience to emergencies in cities and urban areas. The research outcomes provide useful information for designers, etc., to develop pathways for achieving resilient zero-carbon cities in various places.